Sistem Informasi Aplikasi Pemesanan Makanan Restoran Berbasis Web Menggunakan Metode Agile Development - Vendy Blessing Gulo; Agung Triayudi; Agus Iskandar (STMIK Budi Darma, 2023)
In the digital era today, many restaurants struggle in managing their food orders manually, such as recording orders and making payments. This can cause delays in service and errors in order processing. Therefore, it is necessary to develop an efficient and convenient web-based food ordering system for restaurants. The aim of this research is to analyze and develop a web-based food ordering system for restaurants using the efficient and convenient Agile Development method. This method emphasizes team collaboration, continuous development stages, and adjustment to changes that occur during the development process. This research will use the agile method to develop a web-based food ordering system for restaurants that makes it easier for customers to order food and helps the restaurant manage food orders efficiently. The results of the research show that the customer satisfaction level for the web-based food ordering service is 87%. The average ordering time reaches 3 minutes, making the ordering process easierfor customers. Errors in the ordering process occur around 2.5%, with most of them caused by internet connection issues. The security score of the ordering system is 92 out of 100, indicating a good level of security